Stability Analysis of Daihatsu Xenia 1.3 Xi M/T When Turning To Support Smart Driving Program" - HAWARI, NUR MUHAMMAD (2012)
The premise of this research is to estimate the speed of vehicles when turning in certain radius of road, indirectly will support smart driving because the driver can be estimate how fast the vehicle should be run when turning. When vehicles turning arose centrifugal force and moment in the wheel, it can make slip angle in the wheel. The magnitude effect of slip angle wheel decided the stability movement in vehicles. Generally the greater influence of slip angle wheel will disturb the stability of vehicles. On other slip parameter, the most important consider stability is roll axis movement in a vehicle, which condition of occurrence if one in front or rear wheel lift. This research used Daihatsu Xenia 1.3 Xi M/T, the type passenger car. Collected all the data, the writer use two different weight: total weight vehicle (1570 Kg) and Curb vehicle with driver (1100 Kg). Analysisdoneby knowingthe critical speed ofthe vehicle ever in toppling and skidding but withthe sameradius of road which in radius 15 m, 50 m, 110 m, 370 m, 600 m and on the dry and wet condition of asphalt track. for coefficient grip of dry and wet of asphalt track has taken by dry: 0.8 and wet: 0.45. From the calculation and comparison of the critical speed when toppling at 1570 Kg and 1100 Kg vehicles, showed that weight of vehicles has influenced to vehicles begin toppling ever in same radius on the road. The critical speed when skidding for wet and dry condition in different weight (1570 Kg; 1100 Kg) was same for the velocity begin skidding ever in same radius, they had no influenced from weight of vehicle. The most influenced for skidding come from coefficient of grip and radius of road.